A Comparative Analysis of Influences on Choosing a Music Teaching Occupation. (October 2019) - Rickels, David A.; Hoffman, Edward C.; Fredrickson, William E.
The purpose of this study was to compare motivations and influences of high school music students who express an interest in a career in music teaching and those who do not. A previous survey was adapted for the study and administered to a pre-college population that included musicians who stated a preference to pursue music teaching or other music careers and musicians who stated a preference for other nonmusic occupations. Items were analyzed using a discriminant analysis of principal components (DAPC) data reduction strategy, which used a principal components analysis as a first step to determine item loadings onto orthogonal components. The three occupation groups (music teaching, other music, and other nonmusic) were then compared using a discriminant analysis of the resulting components. The model correctly classified 69.8% of cases, with one significant component primarily separating both music groups from the nonmusic career group and three additional significant components separating the music teaching group from the other music careers group. Using this model, the choice of an occupation appears multidimensional, and discrete sources of influence (e.g., music teachers and music teaching experiences explored in prior studies) are not necessarily individually predictive of the overall choice to pursue music teaching.